2004
DOI: 10.1007/s00125-004-1488-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of uncoupling protein-3 mRNA in rat skeletal muscle is acutely stimulated by thiazolidinediones: an exercise-like effect?

Abstract: Aims/hypothesis. We examined whether thiazolidinediones (TZDs) acutely affect uncoupling protein-3 (UCP-3) expression in skeletal muscle and plasma NEFA in Sprague-Dawley rats. Methods. Expression of UCP-3 mRNA in hindlimb muscles and plasma NEFA were measured after a single intraperitoneal injection of TZDs in healthy male rats. Results. Independent of which TZD was injected (50 µmol/kg), UCP-3 expression in gastrocnemius muscle was distinctly increased after 6 h (increase vs vehicle-injected control: pioglit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Gastrocnemius muscle was not investigated because Ucp-3 was not found to be differentially expressed in this tissue. Because UCP-3 is thought to be regulated by PPAR␦ (56) and is found primarily in muscle (11,23), we assessed expression of both proteins in soleus muscle after 24-h unloading. A representative Western blot of UCP-3 and PPAR␦ expression in soleus muscle of three ambulatory and five HLS animals is shown in Fig.…”
Section: Expression Of Ppars and Ppar-interacting And Ppar-regulated mentioning
confidence: 99%
“…Gastrocnemius muscle was not investigated because Ucp-3 was not found to be differentially expressed in this tissue. Because UCP-3 is thought to be regulated by PPAR␦ (56) and is found primarily in muscle (11,23), we assessed expression of both proteins in soleus muscle after 24-h unloading. A representative Western blot of UCP-3 and PPAR␦ expression in soleus muscle of three ambulatory and five HLS animals is shown in Fig.…”
Section: Expression Of Ppars and Ppar-interacting And Ppar-regulated mentioning
confidence: 99%
“…Contradictory results have been reported on the action of thiazolidinediones on UCP3 gene expression in myogenic cells, from inhibition [82] to stimulation [83]. Treatment with thiazolidinediones “in vivo” also led to variable effects depending on the type of thiazolidinedione or the length of treatment [33, 57, 84, 85]. Mice with a muscle-specific PPAR γ deletion show unaltered UCP3 gene expression [86].…”
Section: Pparα and Pparδ Control Ucp3 Gene Expression In Skeletal Musmentioning
confidence: 99%
“…In addition, ligands for RXR which heterodimerises with PPAR, also induce UCP3 mRNA expression [44,81,82]. Also in vivo studies showed that UCP3 mRNA can be induced by PPAR agonists in rodents although the results are less straight forward [83][84][85]. So far, no human data have been published on the effect of PPAR agonists on UCP3, however, we recently found that 8 weeks of rosiglitazone treatment increased UCP3 protein content by $25% in skeletal muscle of human diabetic patients (P. Schrauwen, M. Mensink, G. Schaart, E. Moonen-Kornips, J-P. Sels, E.E.…”
Section: Fatty Acid and Ppar Regulation Of Ucp3 Gene Expressionmentioning
confidence: 99%